Concealed Consent - SM Seyed Fatemi (JRI, 2000)
The issue of consent is an old and controversial question in the field of medical ethics. Nowadays, informed consent is widely considered as a fundamental element in carrying out any medical treatments on a person. Yet some aspects of the issue are blurred and need to be studied more carefully. In the present, article after dealing with three concepts of Expressed Consent, Implied Consent and Concealed Consent, it will be concluded that expressed consent is the sole way to reveal and determine the consent of the person in the field of ART. The main contribution of this article is to discuss the concept of the concealed consent. It is discused that concealed consent is a fiction and thus may not be considered in medical treatments on a person.
Keywords: Consent, Informed consent, Expressed consent, Implied consent, Concealed consent, Medical ethics, Paternalism, Medical paternalism